Teachers’ Role in Learner Autonomy in Large ELT Classrooms - Shrestha, Anita (The EFFORTS, Journal of Education and Research, 2024)
The study aims to find out the role of learners’ autonomy in large ELT class. The learner autonomy is very important and played prominent role in large classroom to make learning effective and interesting and teachers' effectual strategies to generate autonomy in learners. This study adopted qualitative research approach with narrative inquiry design. Five teachers teaching in large classrooms were the respondents. Data for the study were taken by following in-depth interviews as well as the observations of three teachers. The findings suggest that it is very challenging to apply learner autonomy in large number of the students, but it is possible if the teachers have good patterns and techniques to apply it. It also found out that if there are autonomous learners, then the large number of the students don’t exist in trouble in teaching learning activities as it contains various possible intelligence.